Pola Hubungan Desa Adat dan Desa Dinas dalam Penanganan Penduduk Pendatang di Bali - Purwanti, Ni Putu; Sukerti, Ni Nyoman (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 12 No 4 (2023), 2023)
This study aims to find and analyze the relationship patterns of traditional villages and official villages in handling migrants in Bali. The research method is empirical legal research, relying on field data as primary data. The results of the study show that the pattern of the relationship between the traditional village and the official village in handling the immigrant population is synergized so that a harmonious relationship is established in carrying out their respective functions. Regarding the immigrant population, they are divided into immigrants who are Hindu and those who are not, living permanently or temporarily. The Hindu immigrant population is closely related to the local traditional village and the official village, while the non-Hindu are limited to the official village. The attitude of the immigrant population to the policies taken by the traditional village and the official village, the results of the study show that, those who are Hindus in relation to traditional villages, vary widely, some participate as indigenous people and some do not. In relation to the official village, both Hindu and non-Hindu there is no difference. The policies taken, such as security and cleaning fees, are collected every month, the amount of which varies greatly from village to village. The handling of the immigrant population is going in harmony. Penelitian ini bertujuan untuk menemukan dan menganalisis tentang pola hubungan desa adat dan desa dinas dalam penanganan penduduk pendatang di Bali. Metode penelitiannya adalah penelitian hukum empiris, bertumpu pada data lapangan sebagai data primer. Hasil penelitian menunjukan bahwa pola hubungan desa adat dan desa dinas dalam penanganan penduduk pendatang, adanya sinergi sehingga terjalin hubungan yang harmonis dalam mejalankan fungsinya masing-masing.  Terkait penduduk pendatang itu dibedakan menjadi penduduk pendatang yang beragama Hindu dan tidak, tinggal menetap atau sementara. Penduduk pendatang yang beragama Hindu ini erat kaitannya dengan desa adat setempat dan desa dinas, sementara yang non Hindu terbatas pada desa dinas. Sikap penduduk pendatang terhahadap kebijakan yang diambil desa adat dan desa dinas, hasil penelitian menunujukan bahwa, yang beragama Hindu dalam hubungan dengan desa adat, sangat bervariasi, ada yang ikut sebagai warga adat ada juga tidak. Dalam hubungannya dengan desa dinas baik beragama Hindu maupun non Hindu tidak ada perbedaan. Kebijakan yang diambil seperti uang keamanan dan kebersihan yang dipungut setiap bulannya dengan besarannya sangat bervariasi antara desa yang satu dengan yang lainnya. Penanganan penduduk pendatang, berjalan dengan harmonis.